2020
DOI: 10.1021/acs.jced.9b00699
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Solubility Measurement and Modeling of CO2 Absorption in Aqueous Blend of 2-(Diethyl amino) Ethanol and Ethylenediamine

Abstract: The equilibrium CO 2 solubility in an aqueous blend of 2-(diethyl amino) ethanol (DEEA) and ethylenediamine (EDA) was performed at atmospheric pressure with the use of a laboratory scale bubbling absorber. The total concentration of amine blend solution in the range of 1.13−4.90 mol•kg −1 and the EDA mole fraction in the total amine blend in the range of 0.05−0.20 were taken. The experiments for the measurement of CO 2 solubility were performed at a temperature range of 303.15−333.15 K and CO 2 partial pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The heat requirement in the reboiler to regenerate the solvent (reboiler heat duty) is a combination of three key parameters including sensible heat for solvent heat up, heat of vaporization of water, and heat of CO 2 absorption . Among them, the heat of absorption has a significant effect on the total reboiler heat duty . It is important to highlight that although a lower heat of absorption of solvent is desirable from an energy point of view, lower absorption heat does not necessarily mean that the solvent will need lower regeneration energy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat requirement in the reboiler to regenerate the solvent (reboiler heat duty) is a combination of three key parameters including sensible heat for solvent heat up, heat of vaporization of water, and heat of CO 2 absorption . Among them, the heat of absorption has a significant effect on the total reboiler heat duty . It is important to highlight that although a lower heat of absorption of solvent is desirable from an energy point of view, lower absorption heat does not necessarily mean that the solvent will need lower regeneration energy .…”
Section: Resultsmentioning
confidence: 99%
“…62 Among them, the heat of absorption has a significant effect on the total reboiler heat duty. 63 It is important to highlight that although a lower heat of absorption of solvent is desirable from an energy point of view, lower absorption heat does not necessarily mean that the solvent will need lower regeneration energy. 63 Oexmann and Kather 64 stated that considering only heat of absorption is not sufficient, and all three parameters as well as the operating parameters of the whole process should be taken into account.…”
Section: [ ] + [ ] + [ ] + [ ] + [ ] + [ ] + [ ] + [ ] + =mentioning
confidence: 99%
“…The amount of CO 2 captured was proportional to the concentration of the amine solution due to the EDA-CO 2 chemical affinity. Kumar et al [22] proposed the use of EDA as an activator in the CO 2 capture process by increasing the solubility capacity of CO 2 in the amine aqueous solutions (chemical solvents). Snapshots of the aqueous amine solutions were taken at the end of the experiments (see Figure 3d).…”
Section: Co 2 Capture Testing Using Edamentioning
confidence: 99%
“…To our understanding, the double amino group that EDA possesses does not benefit from these concentrations, due to the relative abundance of nitrogen in the EDA molecule (46.59%) compared to the MEA molecule (22.65%) for CO 2 capture applications. Hafizi et al [21], Kumar et al [22], and Nakhjiri and Heydarinasab [23] reported the use of EDA as an additive to improve CO 2 capture processes. Ciftja et al [24], da Silva and Svendsen [25], and Thompson et al [26] analyzed the chemical reaction mechanisms of EDA in CO 2 absorption processes.…”
Section: Introductionmentioning
confidence: 99%